Determinan Pemanfaatan Pelayanan Voluntary Counselling and Testing (VCT) pada Ibu Hamil di Wilayah Kerja Puskesmas Langsat Kota Pekanbaru Tahun 2020 - Irmawati Irmawati; Christine Vita G.P; Zulmeliza Rasyid (Jurnal Kesehatan Komunitas, 2020)
Voluntary Counselling and Testing (VCT) is voluntary counseling and HIV testing which aims to help prevention, caret, and treatment of HIV and AIDS. According to Permenkes No.42 in 2017 about triple elimination explain every pregnant woman must be checked for HIV, Hepatitis B, and Sifilis as early as possible Mother to Child HIV Transmission (MTCT) In 2018, in Indonesia the target of HIV testing in pregnant women is that 60% of pregnant women are tested for HIV. However, only 34% of pregnant women conduct examinations, and the Langsat Health Center is the health center with the lowest VCT rate in pregnant women in Pekanbaru City at 12,7% of pregnant women not to check. The purpose of this study was to determine the determinants of the use of Voluntary Counselling and Testing (VCT) services of pregnant women in the work area of Langsat Health Center Pekanbaru City in 2020. This was an analytical quantitative type with a cross-sectional design. The sampling technique was accidental sampling totaling 101 respondents. Variable of the research were knowledge, attitude, stigma, discrimination, support of family, and support from health workers to the utilization of VCT. Analysis of the data used in univariate and bivariate analysis with chi-square test with α = 0,05. The result showed a variable knowledge (p = 0,010. POR = 3,357), stigma and discrimination (p = 0,042. POR = 2,619), family support (p = 0,002. POR = 4,357), and support of health workers (p = 0,004. POR = 3,843) are related to the use of VCT. Suggestion for the health center to actively socialize about VCT and invite cross-sectoral to collaborate in VCT examination in pregnant women can be easily affordable.